Hubungan Tingkat Kecemasan dan Intensitas Nyeri Haid dengan Konsentrasi Belajar Remaja Putri - Putri Rismawati; Nutrisia Nu’im Haiya; Iwan Ardian; Intan Rismatul Azizah (Lembaga Pengembangan Kinerja Dosen, 2025)
The intensity of menstrual pain in adolescent girls can decrease study concentration due to discomfort and anxiety affected by hormonal changes during menstruation. This study aims to determine the relationship between the level of anxiety and intensity of menstrual pain with adolescent girls' study concentration. This study uses a quantitative method with a cross sectional analytical approach, with a total of 133 respondents determined by the solvin formula. Data collection used three instruments: Anxiety level, intensity of menstrual pain, and study concentration. The data analysis was carried out using the Spearman Rank test with valid and rebable questionnaires. The study showed that there was a significant relationship between anxiety level and learning concentration P-Value = 0.000 and rho = 0.426 while menstrual pain and learning concentration P-Value = 0.000 and rho = 0.515. so it can be concluded that there is a relationship between the level of anxiety and intensity of menstrual pain and the concentration of adolescent girls' learning. This research can increase the role of community nurses in counseling, reproductive education and relaxation training for female students with menstrual pain, anxiety and learning concentration disorders.